Analisis Total Productive Maintenance (TPM) pada Mesin Ketel Uap dengan Menggunakan Metode Overall Equipment Effectiveness (OEE) di PG. XYZ - Anggoro, Rangga Bayu; Muttaqin, Aan Zainal; Susanto, Doni (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the application of Total Productive Maintenance (TPM) on the Steam Boiler machine at PG. XYZ, which plays an important role in the sugar production process. The background of this research is the increasing downtime of the boiler machine, which was recorded at 15.67 hours in 2023 and jumped to 29.76 hours in 2024. The method used is Overall Equipment Effectiveness (OEE) analysis with data collection through observation and interviews on data during the period May - September 2023 and 2024. The research findings show that the highest OEE value reached 97.57% in September 2023, while the lowest value was recorded as 79.88% in August 2024, with an average OEE of 86.98%. Although the Availability value reached 99.26%, the Performance and Quality values were still below World Class standards. The conclusion of this study emphasizes the importance of effective maintenance to improve machine performance and productivity, as well as the need for continuous improvement strategies in the maintenance process.